Dinamika Perilaku Harga dan Integrasi Vertikal Pasar Cabai Merah di Provinsi Kalimantan Barat: Pendekatan Vector Error Correction Model - Fitrianti, Wanti (Universitas Pahlawan Tuanku Tambusai, 2024)
Increased price volatility and weak vertical integration indicate inefficiency in red chili marketing. The efficiency issue is becoming more important because it may boost the well-being of red chili producers while also driving innovation. The study's goal is to investigate the pricing behavior and vertical integration of the red chili market in West Kalimantan. The analysis uses a daily pricing series at the producer, wholesaler, and consumer levels that runs from January 1, 2020, to June 30, 2024. Coefficient variation analysis (CV) is used to analyze the price behavior of red chili, and vertical market integration analysis using the vector error correction model (VECM), impulse response function, and forecast error variance decomposition. The study's findings show high rates of price fluctuation for red chili among producers, wholesalers, and consumers.The study's results show that the market is cointegrated and that wholesaler and consumer pricing significantly impact red chili price formation at the producer (farmer) level in West Kalimantan.